How consumers as aesthetic subjects co-create the aesthetic experience of the retail environment - Nuttavuthisit, Krittinee (Journal of retailing and consumer services, 2014)
The consumer aesthetic experience, diverse and complex, seems to depend on the individual׳s subjective perception. Studies have questioned if this experience can be conceptualized and explained through underlying patterns. Most studies have focused on the properties of aesthetic objects, explaining their influences on consumer responses, while ignoring consumers as aesthetic subjects. Based on the view that consumers seek pleasure out of even the most mundane objects in their everyday consumption, this study explains how consumers interact and formulate aesthetic experiences in the retail environment. This study proposes psychological stances consumers bring to their interactions with the retail.The results fall into the four main themes expressing how consumers co-create their experiences.The findings contribute to understanding of the consumer as aesthetic subject.